1988
DOI: 10.1021/jm00399a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and intramolecular hydrogen bonding and biochemical studies of clitocine, a naturally occurring exocyclic amino nucleoside

Abstract: The total synthesis of clitocine [6-amino-5-nitro-4-(beta-D-ribofuranosylamino)pyrimidine] (1), a nucleoside recently isolated from the mushroom Clitocybe inversa, has been accomplished. Glycosylation of 4,6-diamino-5-nitropyrimidine (4) with 1-O-acetyl-2,3,5-tri-O-benzoyl-D-ribofuranose afforded the protected nucleoside 6-amino-5-nitro-4-[(2,3,5-tri-O-benzoyl-beta-D-ribofuranosyl) amino]pyrimidine (5) in good yield exclusively as the beta-anomer. Deprotection of 5 with NaOMe/MeOH gave 1 as an 11.5:1 mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 8 publications
3
16
0
1
Order By: Relevance
“…Clitocine, (2R,3R,4S,5R)-2-([6-amino-5-nitropyrimidin-4-yl]amino)-5-(hydroxymethyl) tetrahydrofuran-3,4-diol, (Fig. 1B) was synthesized according to a published procedure (Moss et al 1988) in which 4,6-diamino-5-nitropyrimidine was coupled with 1-oacetyl-2,3,5tri-O-benzoyl-D-ribofuranose following the procedure of Vorbrueggen (Niedballa and Vorbruggen 1974). Removal of the benzoyl protecting groups resulted in the nucleoside clitocine in a 92:8 ratio of β/α anomers.…”
Section: Organic Synthesismentioning
confidence: 99%
“…Clitocine, (2R,3R,4S,5R)-2-([6-amino-5-nitropyrimidin-4-yl]amino)-5-(hydroxymethyl) tetrahydrofuran-3,4-diol, (Fig. 1B) was synthesized according to a published procedure (Moss et al 1988) in which 4,6-diamino-5-nitropyrimidine was coupled with 1-oacetyl-2,3,5tri-O-benzoyl-D-ribofuranose following the procedure of Vorbrueggen (Niedballa and Vorbruggen 1974). Removal of the benzoyl protecting groups resulted in the nucleoside clitocine in a 92:8 ratio of β/α anomers.…”
Section: Organic Synthesismentioning
confidence: 99%
“…Some agents extracted from fruits, vegetables, oilseeds, and plant herbs were able to modulate the activity of P-gp [22], [23], [24]. Clitocine, a nucleoside firstly isolated from the mushroom Clitocybe inversa in 1980s, was found to be a substrate and inhibitor of adenosine kinase [25]. Recent years, clitocine was reported to exert an anti-tumor effect in varies cancer cell lines such as Hela and MCF-7 cells, and many derivatives of this compound were also synthesized and examined for their biological properties [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…Clitocine, a nucleoside firstly isolated from the mushroom Clitocybe inversa in 1980s, was found to be a substrate and inhibitor of adenosine kinase [25]. Recent years, clitocine was reported to exert an anti-tumor effect in varies cancer cell lines such as Hela and MCF-7 cells, and many derivatives of this compound were also synthesized and examined for their biological properties [25], [26], [27], [28]. In the present study, we found that clitocine reverse the P-gp associated multidrug resistance in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the glycosidic bond between a sugar and a primary heterocyclic amine is less stable than that of a natural nucleoside in DNA and RNA, a variety of such exo-aminonucleosides from natural or synthetic origins are known. [22,23] If a potential candidate is chemically too unstable to be useful, the corresponding derivative with a carbocyclic sugar replacing the 2'-deoxyribofuranose unit can be considered as a stable alternative. Such nucleosides are easily accessible by synthesis, [24] are structurally isomorphous to natural nucleosides, and are known to base-pair with complementary nucleosides much in the same way as their natural congeners.…”
mentioning
confidence: 99%